Pengaruh Simulasi Kode Biru terhadap Kecepatan Respon dan Keterampilan Resusitasi Jantung Paru (RJP) Perawat - Zaenal, Zaenal; Rahmat, Rezqiqah Aulia; Rante, Anshar; Fitriani.K, Fitriani.K (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Background: Sudden cardiac arrest is a medical emergency that requires immediate action in the form of Cardiopulmonary Resuscitation (CPR). The success of CPR depends heavily on the speed of response and the skills of healthcare workers, particularly nurses as the frontline of care. However, the reality in the field shows that many nurses experience delays in responding and are less than optimal in performing CPR. Code Blue simulation is a training method that can improve preparedness and clinical skills in emergency situations. Objective: To determine the effect of Code Blue simulation on the speed of response and CPR skills of nurses in inpatient wards. Methods: This study used a quasi-experimental design with a pretest-posttest approach without a control group. A total of 30 nurses were selected using purposive sampling. Measurements were taken before and after the Code Blue simulation intervention using a checklist for response speed and CPR skills based on the 2020 AHA guidelines. Data were analyzed using the Wilcoxon test. Results: There was a significant increase in response speed (p=0.000) and CPR skill scores (p=0.000) after participating in the simulation. The average response time decreased from 98.2 seconds to 72.5 seconds, while skills increased from 24.4 to 36.3 (maximum scale of 40). Conclusion: The Code Blue simulation was effective in improving nurses' response speed and CPR skills. This intervention is feasible for routine implementation as a strategy to improve the quality of emergency care in hospitals.